INVESTOR ATTENTION TO SUSTAINABILITY REPORTS: A TEXT ANALYTICS APPROACH USING GLOBAL EQUITY MARKETS - Dwi Kriswantini; Darmawati Darmawati; Amiruddin Amiruddin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to examine investor attention to sustainability reports using a text analytics approach in the context of global equity markets through a literature review. The growing demand for transparency, social responsibility, and corporate sustainability has pushed sustainability reports into becoming an increasingly relevant source of non-financial information for investment decision-making. However, the level of investor attention to sustainability information and the mechanisms by which such information is processed and responded to still show significant variation across markets and institutional contexts. Through a systematic search and analysis of recent academic literature, this study synthesizes key findings related to the role of sustainability reports in attracting investor attention, the development of text analytics in capital market research, and the implications of sustainability information for investor behavior and global equity market performance. The study findings demonstrate that text analytics allows for a more objective measurement of investor attention through the analysis of frequency, sentiment, complexity, and narrative in sustainability reports, which in turn correlate with market reactions, stock liquidity, and information efficiency. This study contributes by presenting an integrated conceptual framework on the relationship between investor attention, sustainability disclosure, and text analytics methods, and identifying research gaps for future empirical studies, particularly in cross-country contexts and global market dynamics.